An ectomycorrhizal symbiosis differently affects host susceptibility to two congeneric fungal pathogens. (June 2019) - Gonthier, Paolo; Giordano, Luana; Zampieri, Elisa; Lione, Guglielmo; Vizzini, Alfredo; Colpaert, Jan V.; Balestrini, Raffaella
Abstract: The role of ectomycorrhizal fungi in modulating host susceptibility to fungal pathogens is poorly known. Pinus sylvestris susceptibility to two congeneric fungal pathogens was compared between mycorrhizal and non-mycorrhizal plants. The ectomycorrhizal fungus was Suillus luteus, while the pathogens were Heterobasidion irregulare and H. annosum . H. irregulare is native to North-America and invasive to Europe, whereas S. luteus and H. annosum are native to Eurasia. Non-mycorrhizal plants were equally susceptible to both pathogens. Mycorrhizal plants were significantly less susceptible to H. annosum than non-mycorrhizal plants, whereas there were no differences when considering H. irregulare . The abundance of ectomycorrhizas was negatively and significantly correlated to the level of host susceptibility only to H. annosum . This study shows that the protective role of ectomycorrhizal fungi may differ when the host is challenged by congeneric fungal pathogens. Results add a further clue to explain and predict the invasiveness of H. irregulare in Europe. Highlights: Ectomycorrhizas differently protect hosts challenged by congeneric fungal pathogens. Host susceptibility to native fungal pathogens depends on ectomycorrhizas abundance. Ectomycorrhizas fail to protect host against the invasive Heterobasidion irregulare .